Microsoft System Center Data Protection Manager 2012 R2 cookbook : over 100 recipes to build your own designs exploring the advanced functionality and features of System Center DPM 2012 R2 - Hedblom, Robert (Packt Publishing, 2015)
If you are a DPM administrator, this book will help you verify your knowledge and provide you with everything you need to know about the 2012 R2 release. No prior knowledge about System Center DPM is required, however some experience of running backups will come in handy.